2014
DOI: 10.4304/tpls.4.2.303-312
|View full text |Cite
|
Sign up to set email alerts
|

De-foreignizing a Sound: Computer-assisted Pronunciation Practice in Learning a Foreign Language

Abstract: This paper examines the use of computer-assisted pronunciation practice in teaching Chinese as a foreign language. The paper is based on the concept of de-foreignizing sounds for a foreign language. Ten participants in 2012 and 40 participants in 2013 from the University of Zimbabwe participated in this study. Participants were recorded producing some Chinese sounds under strict guidance of the teacher, and then edited audios were given back to the participants for their own listening practice. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The findings revealed that the participants who received CAPT were successful in increasing the quality of their pronunciation of words, at least in the short term. The integration of CAPT into the language classroom had positive results on university-level students, as one study showed that more than 75% of the Chinese FL learners had better pronunciation outcomes as a consequence of using CAPT (Mushangwe, 2014). Third, learners' language proficiency in the target language is also an essential factor that affects the use of CAPT for learning pronunciation, along with other variables such as the amount the first and second language is used and the degree of motivation a learner has for learning a FL (Piske et al, 2001).…”
Section: Factors Affecting the Integration Of Captmentioning
confidence: 99%
“…The findings revealed that the participants who received CAPT were successful in increasing the quality of their pronunciation of words, at least in the short term. The integration of CAPT into the language classroom had positive results on university-level students, as one study showed that more than 75% of the Chinese FL learners had better pronunciation outcomes as a consequence of using CAPT (Mushangwe, 2014). Third, learners' language proficiency in the target language is also an essential factor that affects the use of CAPT for learning pronunciation, along with other variables such as the amount the first and second language is used and the degree of motivation a learner has for learning a FL (Piske et al, 2001).…”
Section: Factors Affecting the Integration Of Captmentioning
confidence: 99%